Bisphenol-A Release and Genotoxicity Differences of Three Branded Adhesives Materials - Lydia Winarta; Rahmi Amtha; Boedi O. Roeslan; Himawan Halim (Faculty of Dentistry, Universitas Indonesia, 2015)
Objectives: The objective of the study are to determine BPA release and genotoxicity differences between three adhesives, and to determine the relationship between BPA release and genotoxicity. Methods: Three branded adhesives materials were polimerized in mold and immersed in pH 7 and 4 artificial saliva from 24 to 720 hours. The artificial saliva was tested with spectrofotometry test to see BPA release at 24, 240, 480, and 720 hours, then freeze dried to get solid extract. Combination of the extract and lymphocite culture (male and female) then tested with in vitro cytokinesis-block micronucleus (MN) assay to see genotoxicity level of three adhesives at 24, 240, 480, and 720 hours as well. Results: The highest BPA release occured at 720 hours by Tetric N-Flow: 0,013μg/L; Filtek Z350XT: 0,11μg/L; Flowtain LV: 0,036μg/L respectively. There was a statistically significant difference between BPA release with time (F = 505,98; p=0,00) and brands (F = 147,65; p = 0,00). Time and BPA release interaction also showed a statistically significant difference (F=13,35; p=0,00). Genotoxicity can be seen at 720 hours on Flowtain LV sample (MN frequency: male: 0,044; female: 0,053). Conclusions: The number of BPA release of all brand was increasing from 24 to 720 hours and did not influenced by brands. Genotoxicity can be seen from one of the adhesive brand at 720 hours.There was correlation between BPA leaching and micronucleus frequency. DOI: 10.14693/jdi.v22i3.402